Can an Object Love? - Söderblom Saarela, Ellen (2025)
Philologists not only investigate, but also tell the story of philology – this loving study of the words, the texts, the narratives of the past. Every instance of philological research is accordingly part of its history and we, as philologists, travel along and with the words, perhaps never fully in charge. This series started with a study of Modern Greek literature, written in French and published in 1962, and has then moved primarily back in time through various periods and kinds of texts, until the last volume (2015) landed in Homeric reception studies. In many ways, this journey is symptomatic of Greek Studies at Uppsala University, stretching from Homer to Byzantine times and often even further.With this volume we wish to introduce new and wider perspectives and call attention to our own role as readers and scholars. Because philology, as any reading practice, is situated – in our minds, our bodies, and the world we live in. We can strive for accuracy and objectivity, but we also need to accept that situatedness. Such an approach, long overdue, has rather recently been adapted in a new form usually called autotheory: personal and yet critical readings of (most often) historical works, practiced by thinkers and writers such as Hélène Cixous in her Mother Homer is Dead (Homère est morte, 2014) and Maggie Nelson in The Argonauts (2015). Autotheory challenges our own position as scholars and pressing contemporary social and political concerns such as women’s subjectification and objectification, embodiment, feminism, and neo-liberalism. Re-reading the classics from different perspectives is both vital and unavoidable in a modern world. It is necessary for the survival of the classics, and maybe for our intellectual survival as well. Ingela Nilsson, series editor